Processos de apuração jornalística na cobertura dos conflitos socioambientais Piquiá de Baixo e Cajueiro entre 2015 e 2021 - FERREIRA, Idayane da Silva (2023)
Given the social function of journalism, it is also responsible for the investigation and dissemination of socio-environmental conflicts. Thus, this research seeks to understand the characteristics of the coverage of Environmental Journalism in Maranhão from the socio- environmental conflicts of Piquiá de Baixo (Açailândia - MA) and Cajueiro (São Luís - MA), between 2015 and 2021. important for both communities, such as the evictions in Cajueiro and the visit of the United Nations (UN) Special Rapporteur in the area of “Implications of the environmentally sound management and disposal of hazardous substances and waste” to Piquiá. This is a qualitative, theoretical-methodological research based on the theories of Newsmaking (news production) and Environmental Journalism. In the development of this investigation, bibliographic research, documentary research, Journalistic Content Analysis (ACJ), questionnaire application and in-depth interviews with 6 journalists were adopted as part of the methodology. Among the conclusions of the research it was verified that the socio- environmental conflicts in Maranhão still receive more coverage and space in independent vehicles and that are outside the state than in regional/local commercial vehicles. The environmental journalists who covered the two communities have practical knowledge of Environmental Journalism, that is, they do not have specialized training, but use journalism tools and experience to work in the area. The difficulty of accessing environmental data in the State appears as one of the biggest challenges in covering conflicts in Maranhão, as well as the lack of positioning by companies and the government regarding violations of rights in both communities. In summary, environmental journalists need to deal with the complexity of the issues, the lack of accurate and reliable data, the pressure from different social actors, such as governments, companies and civil society organizations. In addition, they need to be aware of the challenges of the context in which they are working and the limitations linked to journalistic production itself, such as time, space and the importance that vehicles give to journalistic coverage on the subject.